Two Ways of Gathering the Plot to Kill Jesus in John 11.47–53 - Beutler, Johannes (New Testament studies, 1994)
The Johannine text about the decision of the High Priests and the Pharisees to have Jesus killed has so far attracted mainly historical and text-historical interest. Authors enquire about the relation of the text to its synoptic parallels – as Mark 14.1–2 par. – or about some pre-Johannine source lying behind our textual unit. The gathering of the High Priests and Pharisees, their reasoning, and the answer of Caiaphas are mainly attributed to pre-Johannine material, the reflection of the evangelist at the end to John himself or even a post-Johannine hand. The reason for this kind of literary criticism can be found in the idea of a death of Jesus for the ‘scattered children of God’ which seems to be alien to the earlier synoptic or synoptic-like material. The limitation to investigations of this kind leads to the inconvenience that the ‘making’ of the Johannine text as such does not come into focus. It seems to me that the final text merits our first attention, prior to any source or tradition theories. So I shall begin my short paper with a synchronic investigation into our text, followed by a diachronic approach.